Effect of clotting factors concentrates on lymphocyte and neutrophil function in vitro - Ghio, Massimo; Contini, Paola; Ottonello, Luciano; Arduino, Nicoletta; Gringeri, Alessandro; Indiveri, Francesco; Dallegri, Franco; Puppo, Francesco (Thrombosis and Haemostasis, 2003)
Immunological abnormalities have been reported in haemophiliacs. Although infections with HIV, hepatitis and other viruses may contribute to these abnormalities, immune defects are detectable also in HIV seronegative haemophiliacs. It is likely that chronic exposure to extraneous proteins in clotting factor concentrates (CFCs) may play a role in immunomodulation, but the underlying mechanisms remain unclear. The results of the present paper show that: a) soluble HLA class I (sHLA-I), soluble Fas-ligand (sFas-L) and transforming growth factor beta 1 (TGF-β1) are detectable in plasma derived but not in recombinant CFCs; b) the level of sHLA-I and sFas-L is proportional to the grade of CFCs purity whereas TGF-β1 showed very variable levels; c) soluble molecules detected in CFCs exert immunomodulatory effects in vitro like apoptosis induction in Jurkat cells and inhibition of mixed lymphocyte reaction response, antigen-specific lymphocyte cytotoxic activity and neutrophil chemotaxis.
Keywords: Clotting factors concentrates; soluble HLA class I; soluble Fas ligand; transforming growth factor β1